UPAYA-UPAYA EXECUTIVE CHEF DALAM MENINGKATKAN KUALITAS MAKANANDI GRAND ZURI HOTEL KUTA, BALI - I Wayan, Induyoga Aditama; Noviasari, Wahyu; Antara, I Made Agung Rai (HARMONY HOSPITALITY, 2023)
The background of this research is the lack of food quality in the areas of texture, temperature and taste in food. Therefore, the author raised the title Executive Chef's Efforts in Improving Food Quality at Grand Zuri Hotel Kuta Bali. The objectives and benefits of this research are to find out how the efforts, constraints and solutions of the executive chef to overcome the obstacles faced in improving the quality of food at Grand Zuri Hotel Kuta, Bali. In this study the authors used qualitative and quantitative data types obtained from primary data and secondary data. Using research instruments in the form of a check list of observations, interviews, documentation, and using data analysis techniques, namely where this research was obtained from qualitative descriptive data. The results of the discussion of this study are as follows (1) to improve the quality of food, there are several efforts made by executive chefs, namely standards for receiving food ingredients, storing food ingredients, implementing hygiene, and working professionalism of employees. (2) Constraints faced include delays in the delivery of food ingredients, damage to operational equipment and lack of communication between employees. (3) The chef's solutions in overcoming these obstacles include: by giving a warning to the supplier if it is still late in the delivery of food ingredients, by checking equipment at least once a week, and always urging employees to maintain good communication